Neonatal Urinary Ascites: A Report of Three Cases - Adaobi Solarin; Priya Gajjar; Peter Nourse (Case Reports in Nephrology)
Urinary ascites in neonates is not a common condition. Three cases of urinary ascites are presented and each of them has a different aetiology. Neonates with urinary ascites usually present as clinical emergency, requiring resuscitation, ventilator support, and subsequent drainage of urine. The ultimate management depends on the site of extravasation and the underlying cause.